Comparison between Retrograde Flexible Ureteroscopy and Percutaneous Nephrolithotomy for the Treatment of Renal Stones of 2–4 cm - Cozma Cosmin; Dragos Adrian Georgescu; Petrisor Geavlete; Razvan-Ionut Popescu; Bogdan Geavlete (Medicina, 2023)
Background and objectives: Renal stones are widespread, with a lifetime prevalence of 10% in adults. Flexible ureteroscopy enables urologists to treat lower calyx stones or even complex renal stones through the natural orifice and achieve an acceptable stone-free rate. Hence, we analyzed the effectiveness and safety of FURS versus PCNL in treating renal stones between 20 and 40 mm in diameter. Materials and methods: We retrospectively analyzed 250 consecutive patients with large renal solitary stones (stone burden between 2 and 4 cm) from 1 January 2019 to 31 December 2020. The patients were divided into two groups: group 1 (125 patients), in which the patients were treated by a retrograde flexible ureteroscopic approach, and group 2 (125 patients), in which we used percutaneous nephrolithotomy. Stone characteristics and anatomical data were observed based on the computed tomography (CT) and/or KUB (Kidney-ureter-Bladder) radiography imaging archive. Results: The mean stone burden was 26.38 ± 4.453 mm in group 1 and 29.44 ± 4.817 mm in group 2. The stone-free rate after the first ureteroscopy was higher for the PNL(percutaneous nephrolithotomy) group (90.4%) than the F-URS group (68%). After two sessions of ureteroscopy, the SFR was 88.8% in the first group, and after three procedures, the SFR rose to 95.2%. The overall complication rate was higher in group 1 than in group 2 (18.4% vs. 16.8%), but without statistical relevance (p > 0.5). Furthermore, we encountered more grade III and IV complications in the PNL group (8.8% vs. 4.8%, p < 0.05). Conclusion: Flexible ureteroscopy proves to be efficient in treating renal stones over 2 cm. However, the patients must be informed that more than one procedure might be necessary to overcome the entire stone burden.